2023
DOI: 10.3390/molecules28041809
|View full text |Cite
|
Sign up to set email alerts
|

A Status Review on Health-Promoting Properties and Global Regulation of Essential Oils

Abstract: Since ancient times, essential oils (EOs) have been known for their therapeutic potential against many health issues. Recent studies suggest that EOs may contribute to the regulation and modulation of various biomarkers and cellular pathways responsible for metabolic health as well as the development of many diseases, including cancer, obesity, diabetes, cardiovascular diseases, and bacterial infections. During metabolic dysfunction and even infections, the immune system becomes compromised and releases pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 149 publications
0
33
0
Order By: Relevance
“…Obesity is among them, and EOs have been used as complementary treatment. 50 Citrus EOs have been studied for their anti-obesity properties, and in an animal study sweet orange was suggested as a potential dietary supplement for weight loss. Additionally (+)-limonene showed anti-obesity properties.…”
Section: Health Benefits Of Eos In Foodmentioning
confidence: 99%
See 4 more Smart Citations
“…Obesity is among them, and EOs have been used as complementary treatment. 50 Citrus EOs have been studied for their anti-obesity properties, and in an animal study sweet orange was suggested as a potential dietary supplement for weight loss. Additionally (+)-limonene showed anti-obesity properties.…”
Section: Health Benefits Of Eos In Foodmentioning
confidence: 99%
“…Additionally (+)-limonene showed anti-obesity properties. 50 EO constituents could be considered as potential agents for cardiovascular disease prophylaxis. This is related to the concept that aromatic herbs and spices included in the diet in the long term cause positive effects and interrupts the progression of cardiovascular diseases.…”
Section: Health Benefits Of Eos In Foodmentioning
confidence: 99%
See 3 more Smart Citations